Analysis and Field Measurement on the Internal Force Variation Laws of Steel Pipe Columns in Subway Stations - Nan Liu; Yu-sheng Jiang; Hua Jiang; Long-fei Chang; Xing Yang; Xiao Tong (Geofluids)
Steel pipe columns are an important component in subway station construction and with stand stress state and internal force during the construction process. Based on the engineering background of Beijing subway, this paper introduces the geological conditions, station structure types, and internal force monitoring of steel pipe columns of 10 subway stations constructed by the PBA method. The field monitoring indicates that the greatest change in the internal force of the steel pipe column occurs during stage 1 (beam, primary support, and secondary lining buckle arch construction stage), no matter pile foundation station or strip foundation station, which accounts for about 60% to 65% of the total axial force. When the left and right spans are not synchronously arched or excavated, the steel pipe column is subjected to uneven forces and bears a large bending moment is produced. When the depth of overburden is between 7 m and 15 m, the internal force of the steel pipe changes positively correlated with the overburden depth. During the construction process, the internal force of the steel pipe varies widely in the silty sand stratum. Also, the steel pipe columns in stations affected by groundwater bears about twice of the axial force compared with other stations are not affected by groundwater. In addition, the construction period is also a factor that affects changes in internal forces. This research is conducive to update the database of the world subway projects and can serve as a practical reference for similar geological condition.